2018
DOI: 10.1080/0284186x.2018.1503419
|View full text |Cite
|
Sign up to set email alerts
|

Expression of survivin does not appear to influence breast cancer recurrence risk

Abstract: Background: Survivin is an inhibitor of apoptosis, and its expression associates with poor outcomes in multiple cancers. It may be a therapeutic target due to its unique expression in cancer cells. Methods: We estimated the association between nuclear and cytoplasmic survivin expression in primary tumors and breast cancer recurrence. In this case-control study, we included women age 35-69, diagnosed with stage I-III breast cancer between 1985 and 2001, and registered with the Danish Breast Cancer Group. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Additional studies confirm Survivin's association with high tumor grade cancers and recurrence [ 23 ]. The present study identified that HIF-1α and survivin were associated with tumor recurrence, which is consistent with ours Recently, Collin conducted two studies on breast cancer in Danish patients and identified that HIF-1α expression in ER-negative tumors was associated with early recurrence in female patients with breast cancer [ 24 ]; however, survivin expression was not associated with breast cancer recurrence, but the ratio of survivin in the cytoplasm to the nucleus may be associated with recurrence [ 25 ]. The results of the present study differ from those of the Danish study.…”
Section: Discussionsupporting
confidence: 89%
“…Additional studies confirm Survivin's association with high tumor grade cancers and recurrence [ 23 ]. The present study identified that HIF-1α and survivin were associated with tumor recurrence, which is consistent with ours Recently, Collin conducted two studies on breast cancer in Danish patients and identified that HIF-1α expression in ER-negative tumors was associated with early recurrence in female patients with breast cancer [ 24 ]; however, survivin expression was not associated with breast cancer recurrence, but the ratio of survivin in the cytoplasm to the nucleus may be associated with recurrence [ 25 ]. The results of the present study differ from those of the Danish study.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies employed IHC, which allowed visual assessment of BIRC5/survivin protein localization in the cells [ 24 ], but provided no quantitative measures for comparison between samples and the different patient cohorts. Several recent reports presented divergent results in an attempt to use the cellular localization of BIRC5/survivin for prediction of BC recurrence [ 25 , 58 , 59 ]. We demonstrated that BIRC5/survivin analysis on the mRNA or protein levels was sufficiently sensitive to predict clinical outcome, disregarding its cellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis revealed high BIRC5/survivin expression in BC to be predictive for disease-free and overall survival in hormone receptor negative BC [ 24 ]. However, a prospective Danish study was unable to establish a link between BIRC5/survivin expression ratio between the cytoplasm and nucleus, and the recurrence rate in a cohort of ER-positive BC patients [ 25 ]. Nevertheless, overexpression of cytoplasmic BIRC5/survivin was found to be associated with an increased risk of recurrence in ER-negative BC patients [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cells, cytosol survivin has been related to inhibition of apoptosis, while nuclear survivin is more likely to be involved in aberrant proliferation. Collin et al , in a recently published case-control study encompassing a large patient group ( n = 541), did not confirm the association between cytoplasmic or nuclear survivin expression and breast cancer recurrence [ 51 ]. However, some previously conducted meta-analyses have revealed that cytoplasmic survivin overexpression is an unfavourable prognostic factor, while high expression of nuclear survivin has no impact on breast cancer prognosis [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%